Efficient Kidney Exchange: Coincidence of Wants in Markets with Compatibility-Based Preferences - Roth, Alvin E; Sönmez, Tayfun; Ünver, M. Utku (American Economic Review, 2007)
Patients needing kidney transplants may have donors who cannot donate to them because of blood or tissue incompatibility. Incompatible patient-donor pairs can exchange donor kidneys with other pairs only when there is a "double coincidence of wants." Developing infrastructure to perform three-way as well as two-way exchanges will have a substantial effect on the number of transplants that can be arranged. Larger than three-way exchanges have less impact on efficiency. In a general model of type-compatible exchanges, the size of the largest exchanges required to achieve efficiency equals the number of types.